(untitled) (Research, Society and Development, 2022)
Brain stem tumors are not just a single type of tumor, in fact, they are a variety of neoplasms of glial origin (gliomas). They are usually diagnosed in children aged 5 to 9 years. They may have a focal aspect (less than 2 cm) or a diffuse aspect (an infiltrative pattern). The survival of patients with focal gliomas is higher than that of patients with diffuse gliomas and, even if it is a low-grade glioma, life expectancy is a maximum of 15 years. The purpose of this report is to present the case of a six-year-old female patient with a focal brainstem tumor, located in the medulla oblongata, who had a life expectancy beyond those previously reported in the literature. It is not common to find patients whose survival exceeds expectations like the case reported. At the age of six, this patient diagnosed with a focal brainstem glioma located in the medulla oblongata, underwent treatment with chemoradiotherapy and survives. Currently she is 25 years old, with no neurocognitive disorders and with only a few motor alterations in the right side.